Issues of strategic management of Russian innovative organizations’ intellectual property - Irina Rudaya (Управление)
The purpose of this work is to substantiate the necessity of transition to the strategic management of intellectual property in the context of the modern status, goals and tasks of the innovative development of the Russian economy, which have been set out in the Scientific and Technological Development Strategy of the Russian Federation for 2017–2019 as well as in the context of the Main Lines of Activities of the Government of the Russian Federation for the period up to 2024. The main criteria of a successful integration of the Russian innovative economy into the global economy should be involvement of the Russian organizations as technologies owners in the global outsourcing processes as well as the Russian share in the global system of growth and application of the new knowledge – “a saving box” of new inventions and other objects of the industrial property, created as a result of intellectual work. The development process of intellectual property management strategies for assurance of technological leadership in the selected lines of the scientific and technological development is worth of separate research. The paper considers the economic content of the intellectual property as an immaterial capital as well as its role as a factor of creation of unique advantages and assurance of the long-term competitiveness of an innovative organization on the basis of technological leadership. The analysis of a spectrum of innovative strategies has been carried out by use of a matrix “The Novelty of Innovations – the Demand for Intellectual Deliverables”. A sample comparative estimate of innovation resources of Russia and the countries, leading the IP market has been conducted, relying on the Russian and global statistical data. The stages of the transition to the strategic management of the intellectual property of innovative organizations on the basis of the World Intellectual Property Organization’s guidelines and the Russian business practice have been determined.